The relationship between medical students’ interest in learning and their ability to solve mathematical problems: the chain-mediating role of teacher-student relationship and self-efficacy - Li Yang; Li Yang; Jingwen Cui; Yi Zhang (Frontiers in Psychology, 2025)
IntroductionAlthough the impact of learning interest on academic performance has been extensively studied, the chain-mediated mechanism by which medical students’mathematics learning interest influences competence through teacher-student relationships and self-efficacy remains underexplored. Empirical evidence utilizing multi-mediation models to test indirect effects is particularly lacking.MethodsThis study investigated 806 Chinese medical students, assessing problem-solving ability using PISA mathematics items and examining the chain-mediated pathway of teacher-student relationships and mathematics self-efficacy via structural equation modeling (SEM) and bias-corrected bootstrap methods. After controlling for major, grade, and residence.ResultsThe results demonstrated: (1) The direct effect of mathematics learning interest on problem-solving ability was non-significant (effect size = 0.0101, 95% CI [-0.0144, 0.0346]); (2) The independent mediating effect of teacher-student relationships was non-significant (effect size = 0.0083, 95% CI [-0.0114, 0.0196]); (3) The independent mediating effect of mathematics self-efficacy was significant (effect size = 0.0140, 95% CI [0.0003, 0.0286], contribution rate = 40.79%); (4) The chain-mediated pathway of teacher-student relationships → self-efficacy reached significance (effect size = 0.0020, 95% CI [0.0003, 0.0048], contribution rate = 5.68%). The total mediation effect accounted for 70.66% of the total effect.DiscussionThese findings confirm that self-efficacy serves as the critical mechanism translating medical students’ mathematics interest into competence. We recommend enhancing self-efficacy through clinical scenario-based simulation tasks and stepwise training programs, providing theoretical foundations for reforming medical mathematics curricula.